The Statistical Relationship between Industrial Development and Economic Growth: Empirical Evidence from Egypt - Elkalawy, Saad I. A.; Osman, Yousif; Abdelkawy, Nagwa A. A.; Elmotkassi, Tagelsir A. A.; Montash, Abdelhameed A.; Hassan, Hanan Mohamed Ahmed Sulaiman (Journal of Ecohumanism, 2024)
This paper aims to test the statistical relationship between industrial development and economic growth in Egypt. The study relied on the hypothesis that industrialization causes economic growth as measured by real gross domestic product, Also, economic growth causes industrialization, and a standard model was used to test this causal relationship, depending on the co-integration method, and using the error correction model (VECM). The results of the test model came to the existence of a unidirectional causal relationship in the short run from the real added value of the industrial sector to the real GDP, the real value added growth rate of the industrial sector causes the real GDP in the short run, the causal relationship between real GDP and labor supply is bidirectional in the short run, the causal relationship between real GDP and real capital accumulation is unidirectional in the long run from real GDP to real capital accumulation and bidirectional in the short run.